Legal Understanding of Medan City Suburbs Regarding Employed Children Case Study Analysis in West Medan District - Aminudin Aminudin; Muhammad Luthfi Daulay (AT-TAFAHUM: Journal of Islamic Law, 2019)
Indonesia as a state based on the rule of law guarantees the protection and fulfillment of human rights, including children’s rights and the right to decent work as regulated in the 1945 Constitution. However, despite legal protections, child labor remains a persistent issue influenced by economic, social, cultural, and environmental factors. Children who should spend their time learning, playing, and developing physically and mentally are often forced to work due to poverty, family pressure, cultural values, and limited legal awareness. This condition may expose children to exploitation, unsafe working environments, limited educational opportunities, and psychological as well as physical harm. This research aims to analyze legal protection for child laborers, factors causing children to work at an early age, psychological impacts experienced by child workers, and legal sanctions against employers who violate labor regulations. The study employs an empirical legal research method using observation and interviews supported by library research through primary legal materials, legislation, and secondary legal references. The findings indicate that economic hardship is the dominant factor encouraging child labor, while weak legal awareness and cultural acceptance also contribute significantly. Child labor negatively affects children’s physical growth, cognitive development, psychosocial conditions, and access to education. Indonesian laws, particularly Law Number 13 of 2003 concerning Manpower, provide protection and criminal sanctions against violations involving child labor. Therefore, strengthening legal enforcement, increasing public legal awareness, improving educational access, and enhancing government supervision are necessary to reduce child labor and ensure children’s rights are fully protected for sustainable social development.